Peningkatan Kesadaran Deteksi Dini dan Skrining Infeksi Menular Seksual (IMS) pada Kelompok Berisiko Tinggi di Puskesmas Tomuan Kota Pematangsiantar - Kandace Sianipar (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Sexually Transmitted Infections (STIs) remain a significant public health concern due to their potential complications, including infertility, pelvic inflammatory disease, and increased risk of Human Immunodeficiency Virus (HIV) transmission. High-risk groups require regular screening and early detection efforts to prevent the spread of STIs. This Community Service Program aimed to improve knowledge, awareness, and participation among high-risk populations regarding regular STI screening and early detection. Activities included health education, individual counseling, STI screening services, and evaluation through pre-tests and post-tests. The program involved 40 participants classified as high-risk individuals within the service area of Tomuan Public Health Center. The results showed an increase in the average knowledge score from 58.4 before the intervention to 87.9 after the intervention. Furthermore, 92.5% of participants expressed willingness to undergo regular STI screening after the program. The intervention effectively improved awareness regarding the importance of early detection and regular STI screening for disease prevention and control.